Control of Ferrofluid Droplets in Microchannels by Uniform Magnetic Fields - Varma, Vijaykumar B. (2016)
Magnetic droplets are versatile tools for a range of lab-on-a-chip (LoC) applications. The combination of a uniform magnetic field and magnetic droplet offers wireless and programmable manipulation. We performed LoC experiments and numerical studies on ferrofluid droplets under the influence of a uniform magnetic field. The dynamic behavior of flowing ferrofluid droplets was examined. The droplet size, shape, inter-droplet spacing and velocity could be controlled by tuning the magnetic susceptibility of the ferrofluid, the viscosity of the carrier medium, and the flow rates. Our droplet-based micromagnetofluidic numerical model is in good agreement with our experiments. These studies are useful for magnetic droplet control and mixing in a LoC using a uniform magnetic field.